(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
One of the biggest problems small businesses face is obtaining funding, and many of the traditional sources of financing are not available to small businesses. The capital structure of an enterprise is determined by the relationship between its own and borrowed sources of financing. Capital structure can be measured in different ways, and different approaches to understanding and measuring capital structure can be encountered in the literature. The subject of this research is the analysis of the capital structure of small businesses. The aim of this paper is to determine the level of debt of small enterprises in the Republic of Serbia by applying the debt indicators. The main research findings indicate a relatively low level of long-term debt in total sources of financing. These results are in line with the results of other studies, which emphasize that small businesses are more financially risky and that they have difficulty accessing certain sources of financing, especially long-term debt.